The Impact of Students' Impressions of the School Environment andSelf-Discipline Towards the Learning Outcomes for English - Soleh, Rahmat; Karim, Dudung Abdul; Hamdani, Haris (English Teaching and Linguistics Journal (ETLiJ), 2024)
Environmental factors and discipline have an influence on the results of a student's learning at school, especially in English lessons. The purpose of this study was to analyse the impact of students' impression variables on school environment and self-discipline towards the learning outcomes for English. The research method used was the descriptive survey, with a total sample of 60 people, who were taken by random sampling technique. Data collection used a questionnaire that had been validated beforehand. Data analysis used multiple regression, with normality test and linearity test first. The data analysis carried out provides results: 1) There is a significant impact of students' impressions of the school environment and self-discipline together towards the learning outcomes for English. This is evidenced by Sig = 0.000 0.05 and F count = 9.162. Meanwhile, the multiple correlation coefficient is 0.493 with a contribution of 24.3% to English learning outcomes. 2) There is an insignificant impact of students' impression of the school environment towards the learning outcomes for English. It is proven by Sig value = 0.326 0.05 and t count = 0.991. 3) There is a significant impact of students' impression of self-discipline towards the learning outcomes for English. This is evidenced by Sig = 0.017 0.05 and t count = 2.451. The calculation results show an impact of students' impressions of the school environment and self-discipline towards the learning outcomes for English.